Leadership Practices Through Taoist Philosophical Principles and Teachers' Morale in Selected Preschools in Hebei, China - LIU, KAIHUA (Pacific International Journal, 2025)
This study delves into the impact of leadership practices informed by Taoist philosophical principles on the morale of preschool teachers in Hebei, China. The research uncovers a robust positive correlation between the implementation of effective leadership practices and the elevation of teachers' morale, highlighting the indispensable role of leadership in nurturing a favorable educational milieu. Employing a quantitative comparative correlational research design, the investigation scrutinizes the perceptions of teachers regarding pivotal leadership attributes, encompassing self-awareness, self-cultivation, ego transcendence, humility, and ethical decision-making. Additionally, the study assesses the multifaceted dimensions of teachers' morale, spanning from workplace climate and job satisfaction to recognition and support, professional growth opportunities, and the management of workload and stress. The analysis of the collected data precipitates the formulation of a Leadership Development Plan, which outlines targeted activities and strategic initiatives designed to bolster key leadership competencies. This plan is envisioned to cultivate a school culture that is not only supportive and ethical but also deeply invested in the growth and development of its educational workforce.